Mullerian Agenesis/ Mayer-Rokitansky-Kuster-Hauser (MRKH) Syndrome: A Rare Case Report (Faridpur Medical College Journal, 2026)
Background: Mullerian agenesis or Mayer- Rokitansky- Kuster-Hauser (MRKH) syndrome is a congenital malformation characterized by failure of the Mullerian ducts to develop resulting in a missing uterus & aplasia of upper vagina.Case report: Here, we are reporting a case of MRKH syndrome type II in a 22-year-old married female who presented with primary amenorrhoea & painful coitus & was referred to us for pelvic ultrasonography. Absent uterus & upper part of vagina with normal ovaries & left sided ectopic (pelvic) kidney on ultrasonography & normal female hormone levels on hormone analyses confirmed the diagnosis of MRKH syndrome type II.Conclusion: MRKH syndrome can occur with normal endocrine function & secondary sexual characteristics. Ultrasonography & hormone analyses play a vital role in confirming the diagnosis.Faridpur Med. Coll. J. 2026;21(2): 61-63